Exploring the role of pain as an early predictor of category 2 pressure ulcers: a prospective cohort study. Issue 1 (20th January 2017) - Smith, Isabelle L; Brown, Sarah; McGinnis, Elizabeth; Briggs, Michelle; Coleman, Susanne; Dealey, Carol; Muir, Delia; Nelson, E Andrea; Stevenson, Rebecca; Stubbs, Nikki; Wilson, Lyn; Brown, Julia M; et al.
Abstract : Objective: To explore pressure area related pain as a predictor of category ≥2 pressure ulcer (PU) development. Design: Multicentre prospective cohort study. Setting: UK hospital and community settings. Participants inclusion: Consenting acutely ill patients aged ≥18 years, defined as high risk (Braden bedfast/chairfast AND completely immobile/very limited mobility; pressure area related pain or; category 1 PU). Exclusion: Patients too unwell, unable to report pain, 2 or more category ≥2 PUs. Follow-up: Twice weekly for 30 days. Primary and secondary outcome measures: Development and time to development of one or more category ≥2 PUs. Results: Of 3819 screened, 1266 were eligible, 634 patients were recruited, 32 lost to follow-up, providing a 602 analysis population. 152 (25.2%) developed one or more category ≥2 PUs. 464 (77.1%) patients reported pressure area related pain on a healthy, altered or category 1 skin site of whom 130 (28.0%) developed a category ≥2 PU compared with 22 (15.9%) of those without pain. Full stepwise variable selection was used throughout the analyses. (1) Multivariable logistic regression model to assess 9 a priori factors: presence of category 1 PU (OR=3.25, 95% CI (2.17 to 4.86), p<0.0001), alterations to intact skin (OR=1.98, 95% CI (1.30 to 3.00), p=0.0014), pressure area related pain (OR=1.56, 95% CI (0.93 to 2.63), p=0.0931). (2) Multivariable logistic regression model to account for overdispersion: presence of category 1 PU (OR=3.20, 95% CI (2.11 to 4.85), p<0.0001), alterations to intact skin (OR=1.90, 95% CI (1.24 to 2.91), p=0.0032), pressure area related pain (OR=1.85, 95% CI (1.07 to 3.20), p=0.0271), pre-existing category 2 PU (OR=2.09, 95% CI (1.35 to 3.23), p=0.0009), presence of chronic wound (OR=1.66, 95% CI (1.06 to 2.62), p=0.0277), Braden activity (p=0.0476). (3) Accelerated failure time model: presence of category 1 PU (AF=2.32, 95% CI (1.73 to 3.12), p<0.0001), pressure area related pain (AF=2.28, 95% CI (1.59 to 3.27), p<0.0001). (4) 2-level random-intercept logistic regression model: skin status which comprised 2 levels (versus healthy skin); alterations to intact skin (OR=4.65, 95% CI (3.01 to 7.18), p<0.0001), presence of category 1 PU (OR=17.30, 95% CI (11.09 to 27.00), p<0.0001) and pressure area related pain (OR=2.25, 95% CI (1.53 to 3.29), p<0.0001). Conclusions: This is the first study to assess pain as a predictor of category ≥2 PU development. In all 4 models, pain emerged as a risk factor associated with an increased probability of category ≥2 PU development.